Perspektif konsumen pada food pairing less sugar tea RTD dan makanan pendamping dengan metode check all that apply (CATA) - Ayunda Rachmawati; Dase Hunaefi; Dede Robiatul Adawiyah (AGROINTEK, 2024)
Ready-to-drink tea (RTD) is packaged tea that is widely available in supermarkets, one form of which is less sugar tea. Less sugar tea RTD had low sugar claims, ready to serve-consume, and was also consumed with various complementary foods. The combination of less-sugar tea RTD with complementary foods will produce sensory properties if consumed simultaneously, as called food pairing. This study aimed to identify the characteristics of sensory, emotional, and need-state attributes of the combination of less sugar tea RTD and its complementary food. This research was conducted by initial panelist screening, Focus Group Discussion (FGD) to determine sensory attributes, emotions, and need-state, sensory testing conducted by Home Used Test (HUT). The responses obtained were processed using XLSTAT Software and produced a sensory profile, emotions, and needstate food pairing less sugar tea RTD. The results showed that consumers like less sugar tea RTD paired with cassava chips snacks, with sensory attributes i.e., floral aroma, roasted aroma, tea flavor, sweet, astringent, roasted beef aroma, cassava flavor, crunchy, umami, oily mouthfeel, salty aftertaste, and bitter. It’s close to the ideal pairing based on CATA results. This pairing also produces positive emotions (satisfied, adventurous, and energetic) for consumers. While less sugar tea RTD and crackers side dish is dominated by attributes of floral aroma, roasted aroma, tea flavor, sweet, astringent, milky aroma, cheese flavor, crunchy, salty, creamy mouthfeel, salty aftertaste, and bitter aftertaste. Flat, bored, and disappointed as negative emotions arise when consuming less sugar tea with biscuits and crackers. The pair less sugar tea RTD - cassava chips is considered to have overall flavor complexity that produces good harmony compared to other pairs. It’s the best pair according to consumer panelists